Processes of chromium (VI) migration and transformation in chromate production site: A case study from the middle of China. (October 2020) - Wang, Xingrun; Li, Lei; Yan, Xianghua; Meng, Xiaoguang; Chen, Yucheng
Abstract: The migration and redox transformation processes of toxic Cr(VI) in the upper and deep soil of chromate-polluted site are of great importance for the environmental risk control and soil remediation. In this study, soils from surface to deep (around 30–60 m) and the groundwater in a typical abandoned chromate production plant site which has experienced decades of contamination were both sampled and analyzed. The results show that the soil in the leaching workshop of Cr(VI), dichromate transformation workshop and chromium slag dumping ground exhibits severe contamination of chromium and the pollution has extended to the groundwater, causing serious pollution in groundwater too. The vertical migration and transformation of Cr(VI) in the soil layer are mainly affected by the soil permeability, organic matter content and the amount of water passing through the soil layer. During the downward migration, Cr(VI) tends to be retained by the clay layer and further accumulates around the depth of 5–10 m where the concentrations of both hexavalent and total Cr reach maximum values, and then continues to diffuse from the accumulation layer towards the deeper soil. Accompanying with the reduction of Cr(VI) by organic matter in the soil, the Cr(III) exists at various depths. When the depth is below the groundwater level of saturated aquifer, the distribution of chromium in the soil and groundwater reaches leaching and redox equilibrium due to the long-term interaction between the soil and groundwater. Graphical abstract: Image 1 Highlights: The soil and groundwater at chromium (VI) production workshops are severely polluted. Chromium (VI) tends to be retained by the clay layer and peaks at a certain depth. The main factors include soil permeability coefficient, reductant and elution water. The migration and conversion mechanisms of chromium in polluted site are revealed.